Tra nubi, selve, giardini e tassonomie: nuova liuteria elettromeccanica ed elettroacustica nelle pratiche musicali di Mauro Lanza, Andrea Valle e Simone Pappalardo - Guidarini, Luca (Musica/Tecnologia, 2021)
The research presented in this article investigates the artistic practices of Mauro Lanza, Andrea Valle and Simone Pappalardo, with particular attention to the concrete use and the theoretical definition of their new electromechanical and electroacoustics instruments. The paper considers the works Le Nubi non scoppiano per il peso (2011) by Mauro Lanza, the cycle Selva Petrosa (2019-2020) by Andrea Valle, the cycle Systema Naturae (2013-2017) by Andrea Valle and Mauro Lanza, and the performative practice by Simone Pappalardo. Starting from the definition of instrumental apparatus, the discussion presents the organological problems related to the new electromechanical and electroacoustic lutherie, and examines the definitions of electromechanical and electroacoustic instrument. The works of the three composers are analyzed from the point of view of the instrumental equipment, by investigating the algorithmic control techniques of the musical materials that have been used for organizing the instrumental component, and the different signals for controlling the computational component.